Stability of the solutions of a convection–diffusion equation. (May 2019) - Zhan, Huashui; Feng, Zhaosheng
Abstract: A class of non-Newtonian fluid equations with a convection term is considered. If the diffusion coefficient is degenerate on the boundary, the interaction between the convection and diffusion is investigated, and the stability of solutions is established without any boundary condition.